Liderazgo ético y regulación en un escenario empresarial global - Álvarez Arce, José Luis (2011)
In an increasingly integrated global business arena, local singularities still play a crucial role in many aspects. Business ethics is affected by this duality in profound ways. Legislators have tried to provide uniform ethical guidelines for transnational companies. In this effort to streamline the ethical management of the multinational corporation, regulation could be thought of as an attempt to reduce the role of the leader. We argue that this solution mistakenly presumes a high degree of uniformity across countries. In this paper, we consider how different legal traditions can be used to explain the divergences in implementation and configuration of ethics hotlines. We find that although national regulators established a legal standard (Sarbanes Oxley Act) for global companies, significant differences exist across legal traditions, which sometimes go even deeper, to region and country specific nuances. Legal regulation may never substitute a leader in ethical matters.